Urbanisation control around industrial Seveso sites: the French context. (14th January 2008) - Merad, Myriam; Rodrigues, Nelson; Salvi, Olivier
Industrial activity is both an economic lung for a region and a risk generator for the people living in the vicinity of a site. In France, the Toulouse accident highlighted the need to revise the way in which urbanisation control is carried out around industrial sites. Thus, the new law No 2003-699 of 30 July 2003 about the 'prevention of technological and natural risks and the compensation of the damages' has established Technological Risk Prevention Plans (TRPP). These plans aim at reducing vulnerability around Seveso sites by considering the kinetics, the probability and the intensity of the dreaded events. As technical support to decision-makers in risk prevention from both public and private sectors, INERIS has played an important role in the evolution of the French risk prevention plan. In this paper, we will present the TRPP methodology developed so far for Seveso industrial sites, designing a new way for urbanisation control.